Biogeochemical and Hydrological Drivers of Heterogeneous Nutrient Exports From Subterranean Estuaries - Pain, Andrea J.; Martin, Jonathan B.; Young, Caitlin R. (Frontiers in Marine Science, 2021)
Submarine groundwater discharge (SGD) to coastal zones contributes terrestrial freshwater and nutrients that may support harmful algal blooms (HABs). The magnitude of nutrient exports via SGD depends on volumes of fresh groundwater discharge, its chemical composition, and modifications by biogeochemical processing within subterranean estuaries. Thus, the ability to upscale SGD exports requires knowing the range of chemical composition of inland groundwater and how those compositions may be transformed as fresh and saltwater mix within subterranean estuaries. These processes may create heterogeneous magnitudes of solute exports, even at small spatial scales, and such heterogeneities have rarely been assessed for regional or global SGD nutrient export estimates. To evaluate heterogeneity in subterranean estuary processes and nutrient export, we collected seasonal pore water samples in 2015–2016 at three proximal (<20 km) subterranean estuary sites in Indian River Lagoon, FL. Sites have homogenous hydrogeological settings, but differ in land use and coastal features, and include a mangrove site, an urban site, and a site offshore of a natural wetland. All sites exhibit little variation through time in nutrient concentrations and modeled SGD rates. In contrast, each site exhibits significantly different nutrient concentrations of potential fresh groundwater sources, fresh groundwater discharge volumes, and nutrient transformations within subterranean estuaries. Groundwater specific discharge correlates with nutrient concentrations, suggesting that higher residence times in the subterranean estuary increase biogeochemical transformations that reduce anthropogenic nutrient loads but increase in situ nutrient sources derived from organic matter remineralization. The differences in transformations lead to SGD nutrient contributions that differ by orders of magnitude between sites and have N:P ratios that are greater than the Redfield ratio (15) for the mangrove (29) and urban sites (28), but less than the Redfield ratio for the wetland site (8). These results indicate that heterogeneity of both absolute and relative nutrient export via SGD complicates integration of nutrient fluxes across regional coastal zones and evaluations of its impacts to coastal ecosystems. A better understanding of the drivers of heterogeneity, including subterranean estuary processes, land use, coastal topography, and vegetation dynamics could improve assessments of regional nutrient loading and upscaling for estimates of global solute cycles.